Virus diagnosis in tree tomato (iSolanum betaceum/i Cav.) by RT-PCR and transmission electron microscopy in Pichincha and Tungurahua Provinces of Ecuador (2017)
Tree tomato (Solanum betaceum Cav.) is an economically important fruit crop in Ecuador. The symptoms of higher virus-related incidence in plantations located in Pichincha and Tungurahua correspond to yellowing, mosaic, leaf deformation and blistering. This research carried out a diagnosis of the viruses present in these production areas using molecular techniques (RT-PCR) and electron microscopy. The identified viruses belonged to the genera Potyvirus (Potato virus Y; PVY), Polerovirus (Potato leaf roll virus; PLRV) and Tobamovirus (Tomato mosaic virus; ToMV), constituting a viral complex of at least two of the three viruses found. The symptomatology related to PVY was spots with tan or oily appearance and leaf  deformation; in addition to these symptoms, yellowing and chlorosis were related to PLRV. Foliar blistering was related to the occurrence of the three viruses. The results indicated the presence of the three viruses in Tumbaco (Pichincha) and two (PLRV and PVY) in Pelileo (Tungurahua). PLRV was found in the 100% of the total samples, PVY in 50% of the Pelileo’s samples and ToMV only in Tumbaco. ToMV virus has been detected for the first time infecting tree tomato in Ecuador.